The Plant Pathogenic Bacterium Streptomyces scabies Degrades the Aromatic Components of Potato Periderm via the β-Ketoadipate Pathway - Khalil, Mario; Lerat, Sylvain; Beaudoin, Nathalie; Beaulieu, Carole (Frontiers in Microbiology, 2019)
The outer potato periderm layer consists of dead suberized cells. Suberin, a protective biopolymer, is made of a polyaliphatic portion covalently linked to polyaromatic moieties. Evidence accumulates that Streptomyces scabies, the main causal agent of potato common scab, can degrade the suberin aliphatic part but its ability to degrade the aromatic portion has not been documented. This polyaromatic portion is mainly composed of cinnamic acids. In this study, two cinnamates (trans-ferulic or p-coumaric acids) were added to the culture medium of S. scabies strains EF-35 and 87.22. HPLC quantification revealed that both strains efficiently utilized these compounds. A proteomic study coupled with gene expression analysis led to the identification of putative catabolic pathways for cinnamates. Catabolism of both compounds appeared to occur via the β-ketoadipate pathway. Gene SCAB_15301, encoding for a putative vanillate monooxygenase, was partly deleted from S. scabies strain 87.22 genome. The mutant retained its ability to catabolize trans-ferulic acid into vanillate but lost its ability to further degrade the latter compound. When the wild-type mutant and complemented strains were grown in the presence of suberin-enriched potato periderm, accumulation of vanillic acid was observed only in the mutant culture medium. This work presents evidence that S. scabies can degrade not only the aliphatic part of suberin but also the constituents of suberin aromatic portion. This may provide ecological and pathological advantages to S. scabies as a saprophyte and pathogen.